2019
DOI: 10.3390/en12193618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Sizes on the Physical and Mechanical Properties of Briquettes

Abstract: The particle size of coal particles is an important factor affecting the physical and mechanical properties of coal. In this study, uniaxial and triaxial compression tests were conducted to investigate the effects of coal particle size on the physical and mechanical properties of briquettes and their impact mechanism using a rock mechanics test-150B servo system (RMT-150B). The results showed that the uniaxial compression strength, elastic modulus and deformation modulus of briquettes increase when particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…When working with smaller particles there is also an increase in the contact area by decreasing the distance between them, promoting the strong connection of mechanical interlocking forces, chemical forces, solid bridge connection and van der Waals force, which consequently has an influence on the mechanical properties of briquettes [73]. This increase in contact points also facilitates heat transfer, strengthening the bonds between particles, which in turn can give solid fuels a higher apparent density, energy density, durability, axial compression resistance, impact resistance and modulus of elasticity [73][74][75].…”
Section: Effect Of Particle Size On the Production Of Biomass Briquettesmentioning
confidence: 99%
“…When working with smaller particles there is also an increase in the contact area by decreasing the distance between them, promoting the strong connection of mechanical interlocking forces, chemical forces, solid bridge connection and van der Waals force, which consequently has an influence on the mechanical properties of briquettes [73]. This increase in contact points also facilitates heat transfer, strengthening the bonds between particles, which in turn can give solid fuels a higher apparent density, energy density, durability, axial compression resistance, impact resistance and modulus of elasticity [73][74][75].…”
Section: Effect Of Particle Size On the Production Of Biomass Briquettesmentioning
confidence: 99%
“…For instance, the change in the size of some sedimentary rocks rich in joints fundamentally affects the change in the rock bulk modulus [10]. In this regard, Pang et al [11] demonstrated that the bulk modulus of coal increases with a decrease in particle size. Jiang [12] reported that the size of the rock particles affects the rock pore structure, thereby triggering changes in the rock bulk modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al 43 carried out a triaxial experiment on briquette coal samples, and the AE characteristics and damage equation were derived. Pang et al 44 carried out uniaxial and triaxial compression tests on briquette coal samples with different particle sizes and found that their mechanical parameters improved with decreasing particle size.…”
Section: Introductionmentioning
confidence: 99%